Sleep, training load and performance in elite female gymnasts - Dumortier, J.; Mariman, A.; Boone, J.; Delesie, L.; Tobback, E.; Vogelaers, D.; Bourgois, J. G. (European Journal of Sport Science, 2018)
Training load (TL) and recovery should be in optimal balance to obtain maximal performance gains. We aimed to study sleep as a recovery technique and its relationship with TL and performance in elite athletes. Twenty-six elite female artistic gymnasts were divided into an under 13 (n = 6), an under 14 (n = 6), a junior (n = 7; 14-15y) and a senior (=World Championship (WC) competitors, n = 7; =16y) category. Sleep, through sleep logs, and training parameters, using the session Rate of Perceived Exertion (sRPE) scale, were monitored to calculate total sleep time (TST), sleep efficiency (SE), TL, monotony and strain. Performance of WC competitors was evaluated through coach and WC qualification ranking. For the entire group, TST (effect sizes (ES) = -1.12, confidence intervals (CI) = -60:-47, P < .05) and SE (ES = -0.13, CI = -1.40:-0.10, P = .022) were shorter during week than weekend nights. TST and SE were highest in youngest gymnasts (P < .05). TL was lowest in under 13 and senior gymnasts (P < .05), while TL, monotony and strain were highest in junior gymnasts (P < .05). A negative regression was found between TST and TL the day after, while higher TL also led to lower TST the following night (P < .001). For the WC competitors, TST the night before the qualifications was shorter than the mean TST of the WC period (ES = -0.95, CI = -170:24, P = .030). TST correlated with coach ranking (r = -0.857, P = .014). Higher TL correlated with worse WC (r = 0.829, P = .042) and coach (r = 0.893, P = .007) ranking. This research in elite gymnasts indicated associations between decreased TST, augmented TL and inferior performance. Optimizing sleep and TL may therefore represent strategies to enhance performance.